THE ROLE OF ZERO-BASED BUDGETS IN EVALUATING THE FINANCIAL PERFORMANCE OF GOVERNMENT INSTITUTIONS-A FIELD STUDY ON A NUMBER OF IRAQI GOVERNMENTAL INSTITUTIONS (World Economics and Finance Bulletin, 2024)
This study aims to clarify the extent to which zero-based budgets contribute to raising the efficiency of the financial performance of the Iraqi government sector, and to explain the obstacles that limit the application of zero-based budgets in the Iraqi government sector, and to determine the requirements that must be met to prepare zero-based budgets to evaluate the financial performance of Iraqi government institutions to achieve these goals. The researcher prepared a questionnaire directed to a sample of employees working in a number of government institutions. The number of the sample to which the questionnaire was distributed reached (30 individuals). After conducting the field study, the researcher came to prove the hypothesis of the study in addition to a number of results, the most important of which is that the zero-based budget improves exploitation. Optimization of the financial resources of government institutions. Through the zero-based budget, it is possible to evaluate existing government projects and develop a plan for future projects. Finally, given the excellence of government financial performance in that it serves society as a whole, a comprehensive control tool must be applied to evaluate the financial performance as a whole, which is what the zero-based budget provides. The researcher also presented two recommendations: It is necessary to evaluate the financial performance of government institutions, as the deviations and errors that may occur in them affect the financial performance of society as a whole or the specific entity that the government institution serves. When evaluating the financial performance by government institutions, it is necessary to compare the features of the various control tools, including planning budgets. It is recommended The researcher decided to use zero-based budgeting
Keywords: Zero-based budgeting; financial performance; evaluating the financial performance of government institutions.